Oxyfuel combustion in rotary kiln lime production. Issue 4 (8th October 2014) - Eriksson, Matias; Hökfors, Bodil; Backman, Rainer
Abstract The purpose of this article is to study the impact of oxyfuel combustion applied to a rotary kiln producing lime. Aspects of interest are product quality, energy efficiency, stack gas composition, carbon dioxide emissions, and possible benefits related to carbon dioxide capture. The method used is based on multicomponent chemical equilibrium calculations to predict process conditions. A generic model of a rotary kiln for lime production was validated against operational data and literature. This predicting simulation tool is used to calculate chemical compositions for different recirculation cases. The results show that an oxyfuel process could produce a high‐quality lime product. The new process would operate at a lower specific energy consumption thus having also a reduced specific carbon dioxide emission per ton of product ratio. Through some processing, the stack gas from the new process could be suitable for carbon dioxide transport and storage or utilization. The main conclusion of this paper is that lime production with an oxyfuel process is feasible but still needs further study.